Cultural Guidelines for Commercial Production of Purple Passion Plant (Gynura aurantiaca) - Jianjun Chen; Richard J. Henny (EDIS, 2008)
ENH-1079, a 4-page illustrated fact sheet by Jianjun Chen and Richard J. Henny, provides guidelines for commercial production of this colorful, velvety foliage plant: propagation, cultural requirements, common problems, and recommendations for interior use. Includes references. Published by the UF Department of Environmental Horticulture, October 2007.